The Teaching Techniques and Strategies Use by the Dressmaking Teachers Perceive by the Dressmaking Students - Castro, Mary Rose Dancel; Andres, Precious D.; Prestoza, Mark Jhon R. (Asian Journal of Assessment in Teaching and Learning, 2018)
The purpose of this research study was to determine the teaching techniques and strategies use by the dressmaking teachers perceive by the dressmaking students of Reina Mercedes Vocational and Industrial School. This research aims to answer the following: What are the teaching techniques used by the dressmaking teachers? ; What are the strategies used by the dressmaking teachers? ; What are the perception of the dressmaking students of these techniques and strategies of the dressmaking students about effectiveness of selected teaching techniques and strategies of their teachers? Three research questions guided the study. The descriptive quantitative research design was adopted. The stratified random sampling techniques was used to select a sample of 90 students. Research findings showed that the teaching techniques employed by the dressmaking teachers are the following: The teacher sets due date to accomplish the projects/job, The teacher catchers the student’s attention when they are noisy, The Teacher corrects students’ errors and supplies them with the correct answers and The teacher uses concrete examples in delivering the lessons and the teaching strategies used by the dressmaking teachers are the following: The teacher orients the students in maintaining and troubleshooting a sewing machine, The teacher guides the students the proper use of sewing tools and equipment, The teacher motivates the students by giving them credits if they accomplish the task or activity before the deadline, The teacher demonstrates actual drafting, cutting, lay outing demonstration before the students do their work and The teacher assist students in doing their works and the techniques and strategies employed by the dressmaking teachers really help the students in their study.